Transient model of heat transfer and material flow at different stages of friction stir welding process. (January 2017) - Shi, L.; Wu, C.S.
Highlights: A transient model of the whole FSW process is developed and experimentally validated. The model is used to analyze the thermal processes in the plunge stage, dwell stage, welding stage and cooling stage of FSW. A detailed understanding of heat transfer and material flow in the whole FSW process is provided. Effect of process parameters on the heat generation and material flow has been analyzed. Abstract: A better understanding of heat transfer and material flow for different stages (including plunge stage, dwell stage, welding stage, and cooling stage) of friction stir welding process is critical for the tool design and selecting appropriate welding variables. In this study, a transient model is developed to quantitatively analyze the dynamic variations of the heat generation, temperature profile and material flow for different stages of friction stir welding process, and is used to investigate the dependence of these aspects on the process parameters such as welding speed and the tool rotation speed. It is found that the total heat generation increases persistently during the plunge stage and reaches its peak value when the FSW tool shoulder contacts with the top surface of the workpiece. From the peak value, the total heat generation decreases monotonically during the dwell stage before attaining the quasi-steady state in the welding stage. The materials flow analysis predicts that the plastically deformed material in the front of the tool flows in counter-clockwise direction, passes the tool on the retreating side and gets released behind the tool during the welding stage. The model is experimentally validated by comparing the measured tool torque and peak temperature values with the predicted results, which agree well with each other.